Wavelength division multiplexing : a practical engineering guide - Grobe, Klaus; Eiselt, Michael (Telecommunications engineer) (Hoboken, New Jersey : Wiley, 2013)
"In this book, Optical Wavelength Division Multiplexing (WDM) is approached from a strictly practical and application-oriented point of view. Based on the characteristics and constraints of modern fiber-optic components, transport systems and fibers, the text provides relevant rules of thumb and practical hints for technology selection, WDM system and link dimensioning, and also for network-related aspects such as wavelength assignment and resilience mechanisms. Actual 10/40 Gb/s WDM systems are considered, and a preview of the upcoming 100 Gb/s systems and technologies for even higher bit rates is given as well. Key features: Considers WDM from ULH backbone (big picture view) down to PON access (micro view). Includes all major telecom and datacom applications. Provides the relevant background for state-of-the-art and next-gen systems. Offers practical guidelines for system / link engineering."--
"In this book, Optical Wavelength Division Multiplexing (WDM) is approached from a strictly practical and application-oriented point of view"--
3.3.1 Photodiodes3.3.1.1 PIN Photodiodes; 3.3.1.2 Avalanche Photodiodes; 3.3.2 Electronic Amplifiers; 3.3.2.1 TIA; 3.3.2.2 Limiting Amplifier; 3.3.3 Pluggable Transceivers for WDM; 3.4 Digital Electronics; 3.4.1 SERDES; 3.4.1.1 Serializer; 3.4.1.2 Deserializer; 3.4.2 Forward Error Correction; 3.4.2.1 FEC Basics; 3.4.2.2 Cyclic Codes; 3.4.2.3 Code Concatenation and Iterative Decoding; 3.4.3 Electronic Distortion Compensation; References; 4 Nonfiber-Related Effects; 4.1 Linear Cross Talk; 4.2 Noise in Optical Transmission Systems; 4.2.1 Noise in Optical Receivers; 4.2.2 Receiver Sensitivities.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Wavelength division multiplexing; Science -- Wave mechanics; Science -- Waves; Wavelength division multiplexing; SCIENCE -- Waves & Wave Mechanics; Wavelength division multiplexing; Electronic books